Measuring the social support network in autistic clients: development and validation of the Network in Action-Interview - van den Heuvel, Rinske M.; Geurts, Hilde M.; Wensing, Michel; Teunisse, Jan-Pieter (Frontiers in Psychology, 2025)
IntroductionAs social relationships are intertwined with mental health recovery, it is important to address a client’s social support network during mental health interventions. This seems even more important for autistic clients, because research suggests they have on average smaller networks and experience more loneliness than non-autistic individuals. Therefore, an interview assessing the social support network in relation to intervention goals was co-created together with stakeholders (autistic clients, mental healthcare professionals and a mother of an autistic client). In addition, the psychometric properties and acceptability of this Network-in-Action-Interview (NiA-I) were studied as pre-registered (AsPredicted #59767).MethodsThe Nominal Group Technique was used to co-create the NiA-I with stakeholders and it was administered to autistic clients (n = 44) recruited in a highly specialized mental health facility.ResultsNetwork-in-Action-Interview social support scores were significantly correlated with the Multidimensional Scale of Perceived Social Support, indicating sufficient convergent validity. Clients and professionals reported that the NiA-I provided the therapist with greater insight into the client’s social support network. Professionals reported the NiA-I could be improved regarding administration duration.DiscussionThis cross-sectional study shows that the NiA-I is a solid and helpful tool for including the social network in clinical practice. Addressing and including a client’s social support network is important for recovery-focused mental health treatment. The NiA-I can assist professionals in taking such actions.